Pengaruh Diet Kariogenik dan Perilaku Pemeliharaan Kebersihan Gigi & Mulut Terhadap Kejadian Early Childhood Caries di Klungkung, Bali - Mia Ayustina Prasetya; Putu Ika Anggaraeni; Rejeki, Putri; Kadek Linda Yunika Putri (Denta Journal Kedokteran Gigi, 2025)
Background: Early Childhood Caries (ECC) is one of the most common dental and oral diseases occurring in children aged 48-71 months. Several factors can influence the occurrence of dental caries in children, one of which is the consumption of cariogenic foods that easily stick to teeth. These foods are fermented by certain bacteria to form acids, which can lead to plaque formation and damage tooth structures if left unchecked for an extended period. Objective: To examine the influence of cariogenic dietary patterns and dental and oral hygiene habits on ECC in children aged 48-71 months at Kumara Bhuana Saraswati Kindergarten, Klungkung. Materials and Methods: This research employs a quantitative study design with an analytical cross-sectional approach. The sampling technique used was non-probability sampling. The study involved 67 pairs of parents and their children (aged 48-71 months) from Kumara Bhuana Saraswati Kindergarten, Klungkung. Results: This study indicate a correlation with a p-value of <0.05 between the consumption of cariogenic foods with dental and oral hygiene maintenance behavior, and between the consumption of cariogenic foods with incidence of ECC in children aged 48-71 months at Kumara Bhuana Saraswati Kindergarten, Klungkung. Conclusion: There is a significant influence of cariogenic dietary patterns and dental and oral hygiene maintenance behavior on the incidence of Early Childhood Caries (ECC) in children aged 48-71 months at Kumara Bhuana Saraswati Kindergarten, Klungkung. Efforts to reduce ECC cases should focus on promoting healthier dietary choices and improving dental and oral hygiene practices among children and their caregivers.